On the Legal System of Tax Voluntary Disclosure Based on Tax Compliance - Hai, Yan (Journal of Legal Studies, 2023)
To encourage taxpayers to voluntarily disclose their illegal tax acts such as tax evasion and evasion and perform their tax obligations, the tax authorities implement tax voluntary disclosure to encourage them. Tax voluntary disclosure not only increases fiscal revenue, improves the information management ability of tax authorities, but also improves the tax compliance of taxpayers. The United States, Germany, and Australia have all established tax voluntary disclosure systems, and have gained some experience. The Tax Collection and Management Law is being revised, and it is also intended to establish the rule of law for tax voluntary disclosure. Based on China's tax practice and drawing on the advanced experience of other countries' tax voluntary disclosure laws, this article attempts to provide suggestions for improving China's relevant legal systems: (ⅰ) clarify the applicable situations of permanent and temporary tax voluntary disclosure; (ⅱ) Provisions on strengthening early communication between tax authorities and taxpayers; (ⅲ) Standardize the content of voluntary disclosure by taxpayers, including supplementing and correcting information that was not reported or not truthfully reported in previous years, and disclosing tax related information such as overseas financial accounts, assets, offshore structures, etc. as required; (ⅳ) Provide for voluntary disclosure of the legal consequences of tax violations, namely, making up the tax owed and paying the tax interest incurred due to delayed tax payment, but with administrative and criminal liability concessions; (ⅴ) Strengthen the construction of supporting systems, mainly including the protection of taxpayers' tax related information and the strengthening of tax law enforcement.